2019
DOI: 10.3390/plants8110512
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Target-Site Resistance to Glyphosate in an Amaranthus palmeri Population from Argentina and Its Expression at Different Plant Growth Temperatures

Abstract: The mechanism and expression of resistance to glyphosate at different plant growing temperatures was investigated in an Amaranthus palmeri population (VM1) from a soybean field in Vicuña Mackenna, Cordoba, Argentina. Resistance was not due to reduced glyphosate translocation to the meristem or to EPSPS duplication, as reported for most US samples. In contrast, a proline 106 to serine target-site mutation acting additively with EPSPS over-expression (1.8-fold increase) was respectively a major and minor contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 76 publications
2
17
0
Order By: Relevance
“…Furthermore, proline has a positive impact on the activity of enzymes and osmotic adjustment under stress conditions, while protecting enzyme denaturation and modulating osmoregulation [25]. The application of proline-modulated antioxidant enzymes such as peroxidase (POX) and catalase (CAT) in tobacco plants under salinity conditions plays a significant role in protein synthesis and accumulation in plants under stress conditions like drought and salinity in order to enhance the growth characteristics and yield [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, proline has a positive impact on the activity of enzymes and osmotic adjustment under stress conditions, while protecting enzyme denaturation and modulating osmoregulation [25]. The application of proline-modulated antioxidant enzymes such as peroxidase (POX) and catalase (CAT) in tobacco plants under salinity conditions plays a significant role in protein synthesis and accumulation in plants under stress conditions like drought and salinity in order to enhance the growth characteristics and yield [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…This result was different to what is commonly found in the glyphosate-resistant A. palmeri populations in the USA which are predominantly characterised by gene duplication/overexpression 5,18,19 . Kaundun et al tested 115 A. palmeri populations from the Midwestern USA, and none of them contained the P106S mutation 6 . This reflects the use of different weed control practices in Argentina and the USA, although recently, the P106S mutation was also found in Conyza canadensis in the USA 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Prior to this work, a population model of a similar weed species, A. tuberculatus was built, assuming glyphosate resistance as a quantitative trait 31 and the pace of resistance evolution was faster than the current case of A. palmeri in Argentina. The different resistance mechanisms in this Argentine population, together with the insights from the segregation and dose responses of PP, PS and SS genotypes 6 , indicated that it is not always feasible to borrow information from similar or even the same species from other geographic locations for model parameterisation. At the population level, genetic diversity within a weed species could lead to differentiated evolutionary responses to herbicidal as well as agronomic weed control methods 32,33 ; at the community level, species diversity could lead to flora changes and succession of dominant weed species 34 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations